(untitled) (Journal of Pure & Applied Sciences, 2026)
The study aimed to measure the impact of digital institutional integration on the efficiency of tax operations in Libya, with the goal of contributing to the reduction of corruption and tax evasion, as well as identifying the challenges and obstacles facing the process of digital institutional integration within the tax system and proposing ways to overcome them. The study adopted a descriptive and analytical methodology and utilized a questionnaire to gather the views of respondents regarding the issue under investigation. A purposive sample of 67 individuals was selected, representing the study population, consisting of employees and managers of departments or divisions directly involved in tax collection, tax evasion tracking, and performance development within the Tax Authority in the cities of Tripoli, Benghazi, and Sabha. The study concluded that there is a statistically significant positive impact of digital institutional integration on improving the efficiency of the Libyan tax system. It found that digital integration reduces the time required for tax collection, simplifies procedures, and strengthens trust between taxpayers and the tax administration. However, the current coordination between the Tax Authority and other relevant entities (such as customs, banks, and the commercial registry) remains limited in effectiveness, which reduces the ability to detect tax evasion early or to improve the accuracy of tax base estimation.